The Future Of IS/IT Strategic Planning In WCC, Australia - Indra Gamayanto; Asih Rohmani; Florentina Esti Nilasari; Ramadhan Rakhmat Sani (JOINS (Journal of Information System), 2017)
Abstrak WCC (Wollongong City Council) merupakan the best organizations yang berada di Wollongong City, WCC memilki banyak products & services yang dapat membantu Community di Wollongong dalam berbagai aktivitasnya.Dengan perkembangan yang pesat di era globalisasi ini, WCC harus terus mengembangkan dirinya dengan banyak melakukan perubahan yang signifikan agar dapat bertahan di dalam persaingan.Porter’s five forces framework; Scott’s Morton five forces methods dan The 7S’s Of Galliers & Sutherland merupakan tiga metode yang akan membantu WCC untuk dapat berkembang dengan lebih baik di masa depan, dengan dasar pengembangan dari dua journal seperti IT Maturity Paths and Framework; Information systems strategy as practice: Micro strategy and strategizing for IS, akan dapat membantu WCC untuk dapat menemukan IS/IT strategic planning yang tepat. Journal ini akan menghasilkan WCC Future Framework yang merupakan sebuah roadmap jangka panjang agar WCC dapat terus berkembang dan mendapatkan serta memberikan keuntungan pada Community dan Wollongong City. Kata kunci: WCC (Wollongong City Council); Australia; The 7S’s Of Galliers & Sutherland; Porter’s Five Forces; Scott’s Morton Five Forces Methods   Abstract WCC (Wollongong City Council) is the best organizations located in Wollongong City, WCC has many products & services that can help the Community in Wollongong in various activities. Furthermore, the rapid development in this globalization era, the WCC must continue to develop itself with many significant changes in order to survive in the competition. Porter's five forces framework; Scott's Morton five forces methods and The 7S's Of Galliers & Sutherland are three methods that will help the WCC to develop better in the future, on the basis of the development of two journals such as IT Maturity Paths and Framework; Information systems strategy as practice: Micro strategy and strategy for IS, will help the WCC to find the right IS / IT strategic planning. This Journal will produce the WCC Future Framework which is a long-term roadmap for the WCC to continue growing and give a benefit to the Community OfWollongong City. Keywords: WCC (Wollongong City Council); Australia; The 7S’s Of Galliers & Sutherland; Porter’s Five Forces; Scott’s Morton Five Forces Methods